History, language and culture of Kyrgyz in the Republic of Kazakhstan - Shaimerdinova, Н.Г.; Zhiembay, Б.С.; Abdrasimova, А.Е. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2018)
Kazakhstan is a multinational state that populated by representatives of various peoples who speak a variety of languages. Kyrgyz is one of the Turkic peoples who has lived in the Republic of Kazakhstan since ancient times. The article considers the historical information of ethnonyms of Kazakh and Kyrgyz, historical migration of Kyrgyz to the territory of Central Asia, as well as Kazakh-Kyrgyz diverse connections and reasons for Kyrgyz migration to Kazakhstan. On the basis of sociological survey data, sociocultural factors in the sphere of family and kinship relations, language proficiency, development of the ethnic culture of the Kyrgyz diaspora in Kazakhstan are revealed.